2019
DOI: 10.1002/lary.28327
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs in sudden hearing loss

Abstract: Objectives: To compare the circulating microRNA (miRNA) expression profiles between sudden sensory neural hearing loss (SSNHL) patients and age-matched normal hearing controls.Study Design: Prospective cohort multi-center study. Methods: Patients presenting within 28 days of onset of SSNHL were prospectively recruited along with contemporaneous age-matched controls. Pooled sera of four patient (n = 09, mean age = 53.0 years; 07, 55.0; 10, 52.9; 10, 51.6) and two control (09, 51.2 and 03, 50.0) groups were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 39 publications
0
39
1
Order By: Relevance
“…We can only interrogate and infer mRNA regulation, and we do not directly identify genes involved with Menière's disease ( 24 ). Despite this limitation, we know miRNAs play a key mechanistic role in various inner ear pathologies such as sudden hearing loss and inner ear development ( 26 , 27 , 29 , 30 ). Additionally, miRNAs have been identified within all main cellular compartments, exosomes, and cell free components throughout the body and have been successfully used as biomarkers for other neurodegenerative diseases like Alzheimer's and Parkinson's ( 25 , 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We can only interrogate and infer mRNA regulation, and we do not directly identify genes involved with Menière's disease ( 24 ). Despite this limitation, we know miRNAs play a key mechanistic role in various inner ear pathologies such as sudden hearing loss and inner ear development ( 26 , 27 , 29 , 30 ). Additionally, miRNAs have been identified within all main cellular compartments, exosomes, and cell free components throughout the body and have been successfully used as biomarkers for other neurodegenerative diseases like Alzheimer's and Parkinson's ( 25 , 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to further understand miRNA interactions within the human inner ear, we used IPA software to predict potential interactions with genes expressed in a normal hearing human cochlea (GEO Series accession number GSE128505 ) ( 10 , 29 ). Secondly, in order to identify miRNAs that are clinically relevant, we screened the identified miRNA-mRNA interactions for genes that have been identified to play a pathologic role in Meniere's disease in either animal models or population studies ( 30 33 ). Key miRNAs identified were then compared the miRNA expression levels in the serum of patients with Meniere's disease and controls.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown the potential of developing biomarkers for hearing loss with serum analysis of proteins and miRNAs. 19 There is a need for a “liquid biopsy” or an equivalent to evaluate the inner ear in a patient-specific fashion. Perilymph profiling may offer a solution.…”
Section: Discussionmentioning
confidence: 99%
“…Inner ear specific proteins have been found in the serum of animal models of ototoxicity and in human vestibular disease (Liba et al, 2017;Mulry & Parham, 2019;Parham et al, 2019). Serum miRNA associated with sudden sensorineural hearing loss have also been found in humans (Li et al, 2017;Nunez, Wijesinghe, Nabi, Yeh, & Garnis, 2020). It is presently not known either of these is associated with exosomes that have been transported out of the inner ear.…”
Section: Discussionmentioning
confidence: 99%